Capacidade preditiva e prognóstica das características definidoras do diagnóstico de enfermagem icterícia neonatal - Dantas, Anna Virgínia Viana Cardoso (2017)
This study’s aim was to analyze the predictive and prognostic capacity of defining characteristics (DC) on Neonatal jaundice Nursing Diagnosis (ND) in newborns hospitalized in the first 24 hours and were followed up for seven days. Cohort study, performed with 120 newborns hospitalized at the Maternity Assis Chateaubriand-MEAC, in Fortaleza. Including both sexes newborns, from intermediate and intensive care’s unity, in the first 24 hours of life. Excluding those hemodynamically unstable or without clinical conditions for physical examination. Criteria for censorship: newborns who died or were discharged or performed an inter-hospital transfer during the follow-up period. For data collection, two instruments were applied, one for first evaluation and other for accompaniment evaluations. The latent class method was used to estimate the incidence of ND, the sensitivity and specificity of each defining characteristic. For survival analysis, a life table was produced by the Kaplan-Meyer Product-Limit Method. The Cox regression model was used to estimate which DCs were associated with newborns survival time. The research was approved by the Research Ethics Committee of MEAC. The Neonatal jaundice ND was present in 64.91% of newborns; Yellow sclera showed greater percentage value from the 3rd to the 5th day and yellow mucous membranes and hematomas, from the 3rd to the 6th day (79.6%, 75.3%, 70.3%, 73.2% and 74.0%, 78.6%, 79.1%, 83.3%, respectively); Abnormal blood profile presented high frequency. All DC, except Ecchymoses, reported a tendency to proportions increases, as did the ND; Yellow-orange skin color, Yellow mucous membranes and Yellow sclera presents a similar distribution to Neonatal jaundice ND, with higher values in the 3rd day of life and discrete gradual decline until the 7th day; Yellow Sclera and Yellow-orange skin color (Sensitivity: 0.9141 and 0.9742 and Specificity: 1.0000 and 0.7238, respectively) ND best predict. Yellow mucous membranes and hematomas performed high and moderate sensitivity, respectively (0.89894 and 0.7246) and Ecchymosis high specificity (0.9627). There was a high incidence of newborns in this nursing diagnosis per day (risk rate: 90.1%, daily incidence rate: 34.17%); A very low Neonatal jaundice ND survival rate (4.1%), with a median time of 2 days, where 75% of newborns presented jaundice within 3 days of life. Gestational age (rho = 0.249, p = 0.006) and birth weight (rho = 0.191, p = 0.037) presented a directly proportional relationship to the survival time. The yellow sclera presence (RR = 1.99), yellow mucous membranes (RR = 2.05), yellow-orange skin color (RR = 8.08) and female (RR = 1.36) were associated with a higher risk of newborns developing Neonatal jaundice; Presence of hematomas in the skin leads to a reduction in the risk ratio (RR = 0.71). The best predictive capacity for neonatal jaundice ND were yellow sclera and yellow-orange skin color; and the female sex with these same characteristics increased the risk of newborns developing this ND.